431. Enhanced Malaria Surveillance in Greece, 2009–2017. (26th November 2018) - Pervanidou, Danai; Tseroni, Maria; Baka, Agoritsa; Vakali, Annita; Georgakopoulou, Theano; Patsoula, Elina; Vassalou, Evdokia; Diamantopoulos, Vasilis; Panagiotopoulos, Takis; Detsis, Marios; Danis, Kostas; Tsiodras, Sotirios; et al.
Abstract: Background: During 2009–2012, sporadic locally acquired (LA) P. vivax malaria cases and clusters were reported in Greece, a malaria-free country. Evrotas, an agricultural area in southern Greece with large migrant population from the Indian sub-continent, was the most affected area. In 2011–2017, we implemented enhanced malaria surveillance to timely detect and treat cases. Methods: We applied the WHO case definitions for imported, LA, and introduced cases. We raised awareness among clinicians and investigated all reported cases. We actively screened for fever (i) the local population in the place of exposure of LA cases, and (ii) weekly, the migrant population in Evrotas, from April to November every year (active case detection, ACD). We distributed rapid diagnostic tests (RDTs) to enhance local diagnostic capacity. In 2015–2017, we established enhanced malaria surveillance in refugee/migrant hosting centers (RMHC). Results: In 2009–2017, 662 malaria cases were reported (67% P. vivax ); 561 were imported, including 442 (79%) in migrants from endemic countries and 119 in travelers. The median annual number of imported cases in migrants increased from 32 (range 12–64) in 2009–2014 to 85 (range 65–91) in 2015–2017. In 2015–2017, 23% ( n = 55) of all cases in migrants were detected in RMHC or points of entry. In 2011 and 2012, 42 and 20 LA P. vivax cases were reported in Greece, including 36 and 10 cases in Evrotas, respectively, while in 2013–2017, the annual median number of LA P. vivax cases decreased to 6 (range 0–8); all were introduced cases. RDTs contributed to the diagnosis in almost 100% of cases in Evrotas and in 96% of cases in RMHC or points of entry. In Evrotas, during ACD, time from disease onset to diagnosis decreased from 6 days in 2011 to 0.5 days in 2017. Conclusion: Following the 2011–2012 peak of LA cases and the implementation of PH measures, the number of LA cases decreased substantially, despite the increased migrant influx. However, the presence of local competent vectors, combined with cases from malaria-endemic countries, heightens the risk of re-introducing malaria in receptive malaria-free areas. Although resource demanding, enhanced malaria surveillance contributed to minimizing the transmission risk and should be continued. Disclosures: All authors: No reported disclosures.